Health Monitoring For Cantilever Crane Frame Using Residual Error Method - Hadi, Nabil H.; Rashed, Iqbal A. (Al-Khwarizmi Engineering Journal, 2019)
In the present research, a crane frame has been investigated by using finite element method. The damage is simulated by reducing the stiffness of assumed elements with ratios (10% and 20 %) in mid- span of the vertical column in crane frame. The cracked beam with a one-edge and non-propagating crack has been used. Six cases of damage are modeled for crane frame and by introducing cracked elements at different locations with ratio of depth of crack to the height of the beam (a/h) 0.1, 0.20. A FEM program coded in Matlab 6.5 was used to model the numerical simulation of the damage scenarios. The results showed a decreasing in the five natural frequencies from undamaged beam which means the indication of presence of the damage. The direct comparison gives an indication of the damage but the location of the damage, is not detected. The method based on changes in the dynamics characteristics of the beam structures are examined and evaluated for damage scenarios. The results of the analysis indicate that the residual error method performs well in detecting, locating and quantifying damage in single and multiple damage scenarios.